UJI AKTIVITAS ANTIBAKTERI FORMULASI SALEP HIDROKARBON DAUN PEPAYA (Carica papaya L.) SEBAGAI SALAH SATU ALTERNATIF OBAT PENYEMBUH LUKA - Erna Prihandiwati; Anna Khumaira Sari (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Papaya (Carica papaya L) is a plant that can live in various places in Indonesia and requires a relatively short time to grow. Papaya leaves contain karpain alkaloid, karikaksantin, violaksantin, papain, saponins, flavonoids, tannins, karposid and saponins. The compounds that have antibacterial properties are karpain alkaloids. Ointment is one of the pharmaceutical preparations that is suitable for wound healing drugs with papaya leaf extract. This ointment is able to treat infections caused by staphylococcus aureus with great effectiveness and small side effects when compared with the use of chemicals. This study aims to determine the most effective formulations of hydrocarbon base ointment with physical properties test. Papaya leaf extract was obtained by maceration method for five days with 96% ethanol. Macerate is then evaporated with water bath until it becomes a thick extract of papaya leaves. Papaya leaf extract is then formulated at formula 2 and then carried out an antibacterial test with extract concentrations of 5; 10; 20; 30 and 40%. This research is experimental research. The results showed that formula 2 was the most effective based on the physical properties test of the ointment. Antibacterial test results showed that the highest inhibition zone diameter was obtained in the ointment of papaya leaf extract concentration of 40% in the amount of 11.63 ± 0.671441 mm and the smallest in the concentration of 5% in the amount of 5.63 ± 0.550757.